Active Power Line Conditioners - Salvador Pérez Litrán; Patricio Salmeron Revuelta; Jaime Prieto Thomas (Academic Press, 2015)
Active Power Line Conditioners: Design, Simulation and Implementation for Improving Power Quality presents a rigorous theoretical and practical approach to active power line conditioners, one of the subjects of most interest in the field of power quality. Its broad approach offers a journey that will allow power engineering professionals, researchers, and graduate students to learn more about the latest landmarks on the different APLC configurations for load active compensation.By introducing the issues and equipment needs that arise when correcting the lack of power quality in power grids, this book helps define power terms according to the IEEE Standard 1459. Detailed chapters discuss instantaneous reactive power theory and the theoretical framework that enabled the practical development of APLCs, in both its original and modified formulations, along with other proposals. Different APLCs configurations for load compensation are explored, including shunt APF, series APF, hybrid APF, and shunt combined with series APF, also known as UPQC. The book includes simulation examples carefully developed and ready for download from the book’s companion website, along with different case studies where real APLCs have been developed. Finally, the new paradigm brought by the emergence of distribution systems with dispersed generation, such as the use of small power units based on gas technology or renewable energy sources, is discussed in a chapter where mitigation technologies are addressed in a distributed environment.Combines the development of theories, control strategies, and the most widespread practical implementations of active power line conditioners, along with the most recent new approachesDetails updated and practical content on periodic disturbances mitigation technologies with special emphasis on distributed generation systemsIncludes over 28 practical simulation examples in Matlab-Simulink which are available for download at the book’s companion website, with 4 reproducible case studies from real APLCs